Optimization of MOF Synthesis - Meyer, Elazar (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Synthesis optimization of the metal organic framework (MOF) UiO-66 has been carried out using 2-aminoterephthalic acid functional group, a zirconium salt and a modulator grafted into the UiO-66 framework. Reaction parameters such as the effects of temperature, reaction time, the nature of the zirconium salt and the ligand, the molar ratio between the zirconium salt and the ligand, the quantity of the modulator, the solvent and the effect of added water have been investigated. The synthesized MOFs have demonstrated excellent chemical and thermal stability, which ensured them to be used as carriers for drug delivery.